ANALISIS KEMAMPUAN BERBAHASA ANAK MELALUI METODE BERCERITA PADA ANAK USIA SEKOLAH DASAR - Zalia Muspita; Warni; Muchamad Triyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the Storytelling Strategy to Develop Students’ Speaking Skillsat SDN 4 Gereneng. This study aims to determine how students’ speaking skills canbe developed through storytelling. This qualitative research used data collectioninstruments such as observation, interviews, data presentation, and conclusiondrawing. The subjects of this study were 22 people, including twenty second-gradestudents, one principal, and one scond-grade homeroom teacher. The findingsreveal that storytelling as a preparation, implementation, and evaluation. Thisapproach has proven effective in improving students’ speaking fluency, vocabularymastery, intonation, expression, courage, and confidence in public speaking. Thestudy also highlights supporting and inhibiting factors in the implementation process.Therefore, storytelling can be recommended as an effective pedagogical strategyfor imroving speaking skills in elementary school students.